1994
DOI: 10.1002/j.1460-2075.1994.tb06532.x
|View full text |Cite
|
Sign up to set email alerts
|

A mutant cysteinyl-tRNA synthetase affecting timing of chromosomal replication initiation in B. subtilis and conferring resistance to a protein kinase C inhibitor.

Abstract: A Bacilus subdlis mutant spnA95 was isolated as resistant at 30°C to the protein kinase C (PKC) inhibitor, sphinganine, and temperature sensitive for growth. As deduced by flow cytometry measurements, the mutant has a 35% reduced initiation mass at permissive temperature, resulting in initiation of DNA replication much earlier in the cell cycle than in the wild type. This modification is accompanied by a change in cell size, as determined by phase-contrast microscopy and flow cytometry. Therefore, this strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 69 publications
3
13
0
Order By: Relevance
“…Incubation was continued for a further 5 h to complete ongoing replication. A previous paper reported that this drug inhibited replication initiation and cell division simultaneously in B. subtilis cells (40). In fact, the cell length at initiation estimated by flow cytometry corresponded approximately to that obtained previously by an extensive microscopic analysis (41) (data not shown).…”
Section: Methodssupporting
confidence: 86%
“…Incubation was continued for a further 5 h to complete ongoing replication. A previous paper reported that this drug inhibited replication initiation and cell division simultaneously in B. subtilis cells (40). In fact, the cell length at initiation estimated by flow cytometry corresponded approximately to that obtained previously by an extensive microscopic analysis (41) (data not shown).…”
Section: Methodssupporting
confidence: 86%
“…In E. coli and B. subtilis , when Rif are added to the culture, RNA synthesis is inhibited, whereas DNA synthesis continues until all cells complete replication and end up with fully replicated chromosomes. DNA plots of Rif‐treated E. coli and B. subtilis cultures show peaks which correspond to the cell ploidy (Skarstad et al ., ; Seror et al ., ). Our result was similar to those in E. coli and B. subtilis , suggesting that Rif inhibits the initiation but not the progression of DNA replication in S .…”
Section: Resultsmentioning
confidence: 97%
“…Consistent with its potential DNA binding property, the P. falciparum PheRS (PFA0480w) has a nuclear localization signal. The CysRS of B. subtilis (which also contains a DNA binding domain) is believed to play a role in initiating chromosomal replication [58]. Therefore, functional roles for P. falciparum PheRSs may extend from aminoacylation to DNA recognition and replication - a suggestion that requires experimental investigation.…”
Section: Resultsmentioning
confidence: 99%